Die Betreuung der HIV-Positiven in Schwangerschaft und Geburt - Beichert, Matthias; Buchholz, Bernd; Weigel, Michael; Martini, M.; Breitkreutz, Raoul; Melchert, Frank (Zentralblatt für Gynäkologie, 1999)
Mother-to-child (vertical) transmission of the human immunodeficiency virus type-1 (HIV-1) is now the main route of infection in HIV-positive children. Without any medical measures and avoiding breastfeeding the rate of vertical HIV-1-transmission is 15-20% in Europe. The rate of vertical HIV-transmission in the German centers is today approximately 2%. This low risk is the result of interdisciplinary prenatal care, antiretroviral therapy according to the individual risk profile as well as cesarean section before onset of labor, and antiretroviral treatment of neonates in the centers.
Gesehen am 12.04.2022